Hubungan Antara Resiliensi dan Flourishing yang Dimoderasi oleh Dukungan Sosial pada Caregiver Lansia - Betwin Haris SukmaJaya; IGAA Noviekayati; Muchammad Rizal; Amherstia Pasca Rina (Universitas Nahdlatul Ulama Blitar, 2026)
The increasing elderly population in Indonesia creates an urgent need for caregivers who can not only bear the burden of caregivers but also achieve optimal thriving conditions. This study aims to analyze the relationship between resilience and thriving, and examine the role of social support as a moderating variable among elderly caregivers. This quantitative correlational study involved 119 elderly caregivers (54 formal, 65 informal) selected through purposive sampling. Data collection used three instruments: Flourishing Measure (10 items, α=0.782), Connor-Davidson Resilience Scale (23 items, α=0.860), and Social Support Scale (15 items, α=0.818). Data analysis used Moderate Regression Analysis. Resilience showed a significant positive relationship with thriving (Z=6.47, p<0.001). Social support demonstrated a direct effect on thriving (Z=2.63, p=0.009) but was not shown to be a moderator (Z=-1.66, p=0.097). Resilience served as a significant predictor of thriving among elderly caregivers. The effectiveness of social support depends on its alignment with the caregiver's specific needs.